2021
DOI: 10.1039/d1sc01731d
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed cross-electrophile Coupling/C–H alkylation reaction enabled by a mediator generated via C(sp3)–H activation

Abstract: Transition-metal-catalyzed cross-electrophile C(sp2)–(sp3) coupling and C–H alkylation reactions represent two efficient methods for the incorpration of an alkyl group into aromatic rings. Herein, we report a Pd-catalyzed cascade cross-electrophile coupling...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…On the basis of both our aforementioned results and previous studies reported in the literature, 2–11 we proposed a mechanism for the palladium-catalyzed C(sp 3 )–H activation coupling reaction proceeding by a 1,4-Pd shift (Scheme 6). Initially, the Pd (0) catalyst coordinates to substrate 1a providing intermediate A , which undergoes oxidative addition to generate Pd( ii ) intermediate B .…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…On the basis of both our aforementioned results and previous studies reported in the literature, 2–11 we proposed a mechanism for the palladium-catalyzed C(sp 3 )–H activation coupling reaction proceeding by a 1,4-Pd shift (Scheme 6). Initially, the Pd (0) catalyst coordinates to substrate 1a providing intermediate A , which undergoes oxidative addition to generate Pd( ii ) intermediate B .…”
Section: Resultssupporting
confidence: 59%
“…In the past two decades, palladium-catalyzed activation of remote C(sp 3 )–H has emerged as a powerful method for the construction of a variety of C–C bonds, 1 most of which rely on the deployment of the 1,4-palladium shift strategy. 2,5–11 As can be seen in Scheme 1, the in situ -generated diorganopalladacycle A via oxidative addition of Pd(0) to a C(sp 2 )–X bond and further cleavage of the proximate intramolecular C(sp 3 )–H bond leads to potential transformations. Alternatively, the ring-opening of palladacycle A through protonation or oxidative addition/reductive elimination provides an σ-alkylpalladium complex B , hence resulting in an overall 1,4-palladium shift as initially observed by Dyker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to ortho -iodo- tert -butylbenzenes, ortho -iodoanisoles were dialkylated to form ortho -dialkyl anisoles (Scheme ). A methoxy group is sterically smaller than a tert -butyl group, so in the palladacycles derived from a methoxy group, steric clashing with the newly introduced alkyl group is attenuated compared to tert -butyl-derived palladacycles. As a consequence, the second C , C -palladacycles did not undergo reductive elimination, and they reacted with a second alkyl chloride molecule to form dialkylated anisoles as the final products.…”
Section: Intermolecular Reactions Of C(sp2)c(sp3)-palladacyclesmentioning
confidence: 99%
“…Based on the control experiments and related reports, 21,22 a putative mechanism was illustrated in Scheme 3. Firstly, 2-iodoanisole 1a undergoes oxidative addition with Pd(0) to give a Pd( ii ) complex A .…”
mentioning
confidence: 99%